2015
DOI: 10.3109/02699052.2015.1028446
|View full text |Cite
|
Sign up to set email alerts
|

Measuring task performance after acquired brain injury: Construct and concurrent validity of ‘Upper Limb Performance Analysis’

Abstract: This study demonstrated good construct and concurrent validity of the ULPA-TPM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…The benefit of interventions judged by a subjective questionnaire (i.e., MAL scores) appeared greater than that judged by objective outcomes measures (i.e., kinematic data or scales with standardized rating by a therapist). This finding raises questions for future research to compare MAL to quantitative ecological observational measures [1,6], highlighting the importance of using MAL combined with outcome J o u r n a l P r e -p r o o f 13 measures of various ICF levels to ensure objective and comprehensive evaluation of UL impairment on activities of daily living [6,7,10,11].…”
Section: Consideration Of Subjective Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefit of interventions judged by a subjective questionnaire (i.e., MAL scores) appeared greater than that judged by objective outcomes measures (i.e., kinematic data or scales with standardized rating by a therapist). This finding raises questions for future research to compare MAL to quantitative ecological observational measures [1,6], highlighting the importance of using MAL combined with outcome J o u r n a l P r e -p r o o f 13 measures of various ICF levels to ensure objective and comprehensive evaluation of UL impairment on activities of daily living [6,7,10,11].…”
Section: Consideration Of Subjective Measuresmentioning
confidence: 99%
“…Upper-limb (UL) impairment due to neurological loss post-stroke typically includes upper motor neuron syndrome, somatosensory deficit contralateral to the brain lesion and cognitive disorders [1][2][3]. Studies estimate that 50% to 85% of individuals with acute stroke and 50% with chronic stroke present UL impairment [4][5][6], which influences functional ability in task accomplishment and independence, thereby affecting quality of life post-stroke [1,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Stage One: Task Performance Mastery breaks task performance down into a required set of steps and then identifies errors in motor performance. Good construct and concurrent validity of ULPA Task Performance Mastery has been demonstrated [32]. Stage Two: Comparative Analysis of Performance-Motor (CAP-M), which is the focus of this study, identifies the pattern of underlying movement errors observed during task performance.…”
Section: Introductionmentioning
confidence: 99%